Reference Performance Test Methodology for Degradation Assessment of Lithium-Sulfur Batteries. Issue 9 (26th May 2018) - Knap, V.; Stroe, D-I.; Purkayastha, R.; Walus, S.; Auger, D. J.; Fotouhi, A.; Propp, K.
Abstract : Lithium-Sulfur (Li-S) is an emerging battery technology receiving a growing amount of attention due to its potentially high gravimetric energy density, safety, and low production cost. However, there are still some obstacles preventing its swift commercialization. Li-S batteries are driven by different electrochemical processes than commonly used Lithium-ion batteries, which often results in very different behavior. Therefore, the testing and modeling of these systems have to be adjusted to reflect their unique behavior and to prevent possible bias. A methodology for a Reference Performance Test (RPT) for the Li-S batteries is proposed in this study to point out Li-S battery features and provide guidance to users how to deal with them and possible results into standardization. The proposed test methodology is demonstrated for 3.4 Ah Li-S cells aged under different conditions.